(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In anypurchase decision gender plays a significant role. It has long been applied inthe field of marketing by the businessmen to promote their products properly asit helps in positioning and segmentation. It determines the need structure,choices of advertisement to reinforce male or female image, attributes in theproduct, value perceived and response pattern towards the marketing stimuli.The following table describes the distribution of the respondents on the basisof gender. Studies reveals that males are absolutely dominant as they have 88.7per cent share in total respondents and it is quite evident that in Haryanamost of the decisions regarding purchasing of durable are taken by the malemembers. Female constitutes a meager 11.3 per cent of the total respondents,where they have had some role in decision making. Since sample constitute ofthose respondents who possess at least one of the consumer durables. So, it isimportant to know that which consumer durables are mostly used by the ruraliteswhich will help marketers in determining their marketing strategies. Thefollowing table shows the distribution of the respondents on the basis of theirpossession of durables. It depicts that thepercentage of the respondents possessing televisions is highest, as it constitutes96.7 per cent of the respondents, followed by Two-wheelers and Refrigerator asthese are possessed by 82.3 and 77.3 per cent of the respondents respectively.Small number of ruralites possess washing machine with 28.3 per centrespondents. The observations shows that media in form of television hasmade in roads into rural India which is a significant development clearlyindicating towards growing interest of ruralites towards outside world in formof entertainment, news items and sports etc.